The problem of acquittal of mass violence is in the history (Journal of Philosophy Culture and Political Science, 2015)
In this article the socially-philosophical analysis of acquittal of massviolence comes true in history of humanity from the epoch of primitivesocieties to our days. To our opinion, the problem of acquittal of massviolence takes the sources from the period of the archaic primitive communalsystem. Exactly then violence was the return reaction of individualon the calls of daily dangers both from the side of fellow tribesmen andfrom the side of neighbours. With flow of millenniums, already in the periodof slave-holding history social violence began to find mass character.So slave-holding civilizations of Ancient East (Egypt, Babylon, India,China) erected oppressing of wide layers of ordinary farmers in the gradeof public policy.Exactly thereafter there is acquittal of the mass violencesent to maintenance of slave-holding state mechanism. The countries ofantiquity (ancient Greece and Rome) managed to attach acquittal of massviolence in the sphere of intergovernmental relations, putting beginning ofepoch of large aggressive wars. Middle ages (V – XV c.) marked by itselfthe unprecedented raging of the mass violence actively fed by the actionsof monarchs (enslaving of peasants, increase of taxes) and catholic church(cross hikes, inquisition).
Keywords: aggression; social violence; punitive measures; legitimity; revolution; compulsion; worldwide policy; terrorism.